2012
DOI: 10.1016/j.jbiomech.2012.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Functional foot symmetry and its relation to lower extremity physical performance in older adults: The Framingham Foot Study

Abstract: Background While many studies use gait symmetry as a marker of healthy gait, the evidence that gait symmetry exists is limited. Because gait symmetry is thought to arise through laterality (i.e., limb preference) and affects gait retraining efforts, it is important to understand if symmetry exists during gait in older adults. Therefore, the purpose of this study was to evaluate foot and gait symmetry in the population-based Framingham Foot Study as well as to determine the effects of vertical force symmetry on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Riskowski et al [21] found that asymmetric foot function and the degree of asymmetry became reduced with advancing age. Based on our findings, there were strong correlations in TGS between the different sides of the body for both sexes, although an increasing asymmetry was observed with age for men but not for women.…”
Section: Discussionmentioning
confidence: 99%
“…Riskowski et al [21] found that asymmetric foot function and the degree of asymmetry became reduced with advancing age. Based on our findings, there were strong correlations in TGS between the different sides of the body for both sexes, although an increasing asymmetry was observed with age for men but not for women.…”
Section: Discussionmentioning
confidence: 99%
“…However, random error would only serve to obscure weaker relations in these data rather than create false positive associations [33]. Moreover, the large study sample greatly mitigates this issue, as it is more than sufficiently powered even with a single scan [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Further, although other studies have suggested that multiple trials may be required for a reliable measure using the Tekscan Matscan (), given the large participant numbers only 1 scan per foot was collected. However, in prior work on the Framingham Foot Study, it was noted that with a reliability of 0.50 (Metscan reliability measures noted as >0.70) (), a sample size of <300 participants was needed to appropriately power the study (). Therefore, due to the higher sample size of our study, we are confident that the findings noted are not an artifact of the single scan of each foot and that the study was adequately powered given the single assessment of foot posture and foot function.…”
Section: Discussionmentioning
confidence: 99%